2012
DOI: 10.3138/ptc.2011-19
|View full text |Cite
|
Sign up to set email alerts
|

Weekend Physiotherapy Practice in Community Hospitals in Canada

Abstract: Purpose: To analyze weekend physiotherapy services in acute-care community hospitals across Canada. Method: Questionnaires were mailed to acutecare community hospitals (institutions with >100 inpatient beds, excluding psychiatric, mental health, paediatric, rehabilitation, tertiary, and long-term care facilities) across Canada from January to April 2010. The questionnaire collected information on patient referral criteria, staffing, workload, and compensation for weekend physiotherapy services and on the avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
0
14
1
Order By: Relevance
“…Ottensmeyer and colleagues found that only 69% of such hospitals nationwide offer WPT, with a wide variation from 93% in British Columbia to 30% in Quebec. 1 These percentages are lower than those found in a recent survey of Canadian tertiary hospitals (97% of 36), 2 a difference that could easily be explained by the differing hospital types and the correspondingly different (i.e., lower-acuity) patient populations, as hospitals with a high proportion of acute-care beds were more likely to supply WPT. 1 However, since the authors excluded from their study hospitals that might not be expected to offer WPT (psychiatric hospitals, long-term care facilities, small hospitals with <100 beds, etc.…”
contrasting
confidence: 47%
See 3 more Smart Citations
“…Ottensmeyer and colleagues found that only 69% of such hospitals nationwide offer WPT, with a wide variation from 93% in British Columbia to 30% in Quebec. 1 These percentages are lower than those found in a recent survey of Canadian tertiary hospitals (97% of 36), 2 a difference that could easily be explained by the differing hospital types and the correspondingly different (i.e., lower-acuity) patient populations, as hospitals with a high proportion of acute-care beds were more likely to supply WPT. 1 However, since the authors excluded from their study hospitals that might not be expected to offer WPT (psychiatric hospitals, long-term care facilities, small hospitals with <100 beds, etc.…”
contrasting
confidence: 47%
“…Sadly, evidence supporting the value of WPT is still lacking. 1,3,4 There are things we do know, however, such as that bed rest has adverse effects on nearly the whole body, 5 including increased muscle atrophy, decreased cardiopulmonary function, and a decreased level of self-care. 6,7 Even in healthy people, bed rest can induce increased insulin resistance and microvascular dysfunction.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Improving Saturday and Sunday AHP services may facilitate an improvement in quality of care in line with the national care guidelines, as well as yield better patient outcomes [8]. Previous research has shown that the availability of weekend physiotherapy services is variable [20], but that these services have the potential to reduce length of stay and improve functional recovery in hip fracture patients [21]. There is also an association between the intensity and frequency of geriatrician input and improved survival of patients with hip fracture [22][23][24].…”
Section: Discussionmentioning
confidence: 99%